Aplicación del proceso de atención de enfermería en un recién nacido de 36 semanas con diagnóstico de shock séptico neonatal en el área de UCIN en el Hospital Alfredo Noboa Montenegro. - Suconota Sicha, Jenny Elizabeth (2020)
The following clinical case was carried out with the purpose of analyzing neonatal septic shock from a holistic perspective, the findings found in the patient are suggestive of a complex pathology, the patient is a 36-week-old newborn gestational calculated from date of last menstruation with clinical diagnosis of septic shock of abdominal focus admitted to the Neonatal Intensive Care Unit of the General Alfredo Noboa Montenegro Hospital located in the Province of Bolívar canton Guaranda. Symptoms started abruptly with the appearance of unquantified thermal rise, diarrhea depositions in moderate quantity and yellowish ocular secretion in the right eye. The physical assessment shows mild neurological deterioration, remains sleepy with weak crying, slight movements, weak suction. Heart rate of 145 per minute and increased respiratory pattern 65 breaths per minute accompanied by slight intercostal circulation. Receiving intravenous antibiotics jaundice is maintained in Zone II according to the Kramer scale. It maintains an oxygen saturation in 89% without ventilatory support, so that oxygen is administered at 0.5 L per hour by pediatric nasal cannula, antipyretic medication is administered plus the application of physical means to lower body temperature. The presumptive diagnosis is an early sepsis, then the differential diagnosis was made that included enteritis, severe acute pancreatitis and hypovolemic shock; Due to the symptoms presented and the laboratory tests, the diagnosis of septic shock of abdominal focus was formulated.